REASONS CAUSING FINANCIAL CRISIS AND ITS THEORETICAL BASIS - Iordanashvili, Lela (European Scientific Journal, ESJ, 2014)
Under conditions of market economy, finances are not definitive for dynamic development of business. During absence of finances there will be economic deformation and incorrect management of finances will create crisis and destabilization. From the second half of 2008 Global financial crisis began to aggravate by unseen scales and temps after great depression of the past century. It achieved its peak in September of 2008, and on October 13, 2008, according to many economists, global financial system appeared to be on the verge of ruins. As a result of world crisis, almost all developed and developing countries appeared to be in economic recession. In comparison to 2007, in 2008 world economic growth was reduced to 3.1 percents. Global recession has sensitively reduced volumes of the world trade, reduction of demand on the most important markets of the world, mainly in the USA and EU zone caused reduction of international prices. Together with reduction of world production decrease of international prices has assisted disinflation processes, and many countries appeared before the challenge of struggle with deflation1. Financial and economic crisis has conditioned taking of unprecedented measures by many countries of the world. They began to conduct not only monetary policy, but also realization of fiscal stimulation programs. As a result, nowadays, question of stability of the world financial system is not under danger.